Figure of merit for divertor protection in the preliminary design of the EU-DEMO reactor. (29th August 2019) - Siccinio, M.; Federici, G.; Kembleton, R.; Lux, H.; Maviglia, F.; Morris, J.
Abstract: This paper discusses the criteria to be used in the preliminary design phases of the EU-DEMO reactor to ensure the performance of the divertor without compromising the stability of core plasma or the fusion power generation. This work refers to a lower single null conventional divertor using actively cooled solid metal plasma-facing components and with extrinsic seeding for heat flux dissipation, which is the solution currently being adopted for EU-DEMO. The analysis does not consider the role of edge localised modes, and also neglects major off-normal events like disruptions. It is shown that it is necessary to fulfil two high-level requirements, namely: (i) the concentration of seeded impurities has to be lower than some critical value in order to not compromise the fusion plasma performance or stability and (ii) damage to the divertor plate in the case of accidental plasma reattachment must be avoided for a sufficiently long time in order to ensure safe, controlled termination of the plasma discharge. These requirements are needed because in a device like EU-DEMO, other strategies relying on mass injection are considered more likely to cause a loss of plasma stability at full current, with dramatic consequences for the integrity of plasma facing components. Two figures of merit, corresponding to these criteria, have been identified in the existing literature and discussed. The dependence of such figures of merit on the relevant machine parameters (major radius and toroidal magnetic field) is analysed. Initially, the analysis is carried out using a simple 0D physics approach and subsequently by means of the systems code PROCESS, which allows for consideration of further parameters, such as aspect ratio and elongation. The main conclusion of the present work is that the simultaneous fulfilment of both requirements limits the viable EU-DEMO size both in terms of major radius and in terms of toroidal magnetic field . Finally, an attempt to extend the EU-DEMO related conclusions to a more general level is made.